Taxonomic reclassification of the fungal pathogen causing dry berry disease of caneberries into the division Ascomycota as Monilinia rubi - Weldon, Bill; McGhee, Gayle C; Jones, Lisa A; Stockwell, Virginia (Plant disease, 2022)
As molecular genetic techniques improve and sequence data become available for more fungal species, taxonomic classifications historically based upon growth morphology alone are being revisited and occasionally reclassified. Herein, we present such an instance for the fungal pathogen that causes dry berry disease of caneberries. The organism was previously described as the basidiomycete fungus based upon the pathogen's production of Rhizoctonia-like angular branching hyphae. Utilizing molecular genetic techniques unavailable when the pathogen was first characterized in 1959, three housekeeping gene regions (ITS, β-tubulin, and G3PDH) were sequenced across 13 contemporary dry berry isolates, as well as the original 1959 type strain, CBS382.59. The resulting neighbor-joining, maximum likelihood, and Bayesian phylogenies for single and multi-locus sequences provide strong evidence that the dry berry pathogen was misclassified. This data, in addition to revisiting macroscopic and microscopic growth morphology, again comparing contemporary dry berry isolates to the CBS382.59 type strain, suggests that the causal organism is a new species within the genus that we propose be classified as . A transition from designation as a basidiomycete fungus to an ascomycete fungus could have implications on chemical management decisions, as well as the assumptions made about cell structure and the pathogens putative life cycle.